2021
DOI: 10.3390/pathogens10020205
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Phenotypic Analysis of Multidrug-Resistant Acinetobacter baumannii Clinical Isolates Carrying Different Types of CRISPR/Cas Systems

Abstract: Acinetobacter baumannii is an opportunistic pathogen being one of the most important causative agents of a wide range of nosocomial infections associated with multidrug resistance and high mortality rate. This study presents a multiparametric and correlation analyses of clinical multidrug-resistant A. baumannii isolates using short- and long-read whole-genome sequencing, which allowed us to reveal specific characteristics of the isolates with different CRISPR/Cas systems. We also compared antibiotic resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 53 publications
2
33
0
Order By: Relevance
“…On the one hand, because most of these isolates are within clinical settings (under constant use of antibiotics) this will select for the presence of (at least some) ARGs. On the other hand, A. baumannii has defence mechanisms, for instance CRISPR/Cas systems or restrictionmodification systems, that can impair the introduction of the mobile genetic elements harbouring the ARGs [10,11]. In this regard, a recent study has shown that a group of A. baumannii having functional CRISPR/Cas systems have considerably fewer plasmids [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, because most of these isolates are within clinical settings (under constant use of antibiotics) this will select for the presence of (at least some) ARGs. On the other hand, A. baumannii has defence mechanisms, for instance CRISPR/Cas systems or restrictionmodification systems, that can impair the introduction of the mobile genetic elements harbouring the ARGs [10,11]. In this regard, a recent study has shown that a group of A. baumannii having functional CRISPR/Cas systems have considerably fewer plasmids [10].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, A. baumannii has defence mechanisms, for instance CRISPR/Cas systems or restriction-modification systems, that can impair the introduction of the mobile genetic elements harbouring the ARGs [10, 11]. In this regard, a recent study has shown that a group of A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of isolates involved in the initial screening was 145, and 49 of them were sequenced. Earlier we have investigated the properties of the CRISPR/Cas arrays and systems for some of these isolates and a set of reference isolates from RefSeq [ 56 ]. Then we carefully selected nine isolates from the initial set, which represented the diversity of the A. baumannii international clones revealed in the hospital, and performed long-read sequencing for them.…”
Section: Methodsmentioning
confidence: 99%
“…They showed that CRISPR/Cas systems in the genomes studied contributed to phage resistance, rather than hampering the horizontal transfer of beneficial mobile genetic elements, including resistance genes. However, there are some works on Acinetobacter baumannii , Enterococcus faecalis , Streptococcus pneumoniae and Staphylococcus aureus that show the direct involvement of CRISPR/Cas systems in the interruption of the horizontal gene transfer [ 13 , 14 , 15 ]. The analysis of correlations between the CRISPR/Cas, anti-CRISPR, and antibiotic resistance gene content of more than 100,000 reference genomes of 5677 different species, including P. aeruginosa , allowed hypothesizing that the selection for antibiotic resistance could result in an accumulation of anti-CRISPR genes in the genomes that harbored both CRISPR/Cas systems and antibiotic resistance genes acquired by horizontal transfer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%